Electrocardiography can be a clue to underlying cardiomyopathy - Malik, Atiullah Imran; Mangudkar, Sangram; Ponvijaya, Yadav; Gokhale, Vijayashree (International Journal of Advances in Medicine, 2021)
Background: Electrocardiography (ECG) is an accessible, low cost diagnostic and prognostic tool. Recent studies have shown increased risk of deaths associated with cardiomyopathy and to study the patients with symptoms of cardiomyopathy on basis of ECG. Methods: A total of 50 patients were explained the procedure and the purpose of the study, informed consent was taken from the patient or the relative in a language they can understand. Required physical examination and necessary investigations were carried out. In our study, maximum subjects had normal voltage (80%) low voltage ECG findings were in 20%, normal QRS complex in 78%, wide QRS complex in 20% LBBB/RBBB in 24%. Evidence of ischemia like T wave changes in 34%, ST wave changes in 24% and tachycardia (26%). Thus ECG can give a clue for diagnosing cardiomyopathy and guide us for further managements but it is not a diagnostic marker for it since most of the patients had normal ECG findings. Results: In our study, electrocardiogram findings among patients are: Maximum subjects had normal voltage (80%). Low voltage ECG findings were in 20%. Normal QRS complex in 78%, wide QRS complex in 20% LBBB/RBBB in 24%. Evidence of ischemia in 58% and tachycardia (26%). Conclusions: ECG is an accessible, low cost diagnostic and prognostic tool. Most common findings in cardiomyopathy is biventricular hypertrophy and left bundle branch block with wide QRS complex, low voltage ECG and ST changes as also seen in present study. Thus, ECG can be initial investigation for cardiomyopathy and can give us clue for further investigations and management.